Overweight/obesity and chronic health conditions in older people with intellectual disability in Ireland - Mc Carron, Mary; Burke, Eilish (My University, 2021)
Background: This study examines overweight/obesity and chronic health conditions (CHCs) in older people with intellectual disability (ID). Methods: Data for this cross-sectional observational study emanated from Wave 2 of the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing, a longitudinal study assessing the health and well-being of older Irish adults with ID aged ≥40 years across all levels of ID. Participation involves an interview process and collation of objective health measures. In this study, body mass index (BMI) (n = 572), used as a measure of weight status, was examined with clustered doctor’s diagnosed CHCs. Descriptive analysis was conducted where counts (n) and proportions (%) were used to summarise the variables univariately, while cross-tabulations were used for bivariate summary into counts and proportions. With overweight/obesity prevalence established and patterns described using logistical regression, Pearson’s chi-squared test was used to test for significant associations. Results: Overweight/obesity identified in 69% of participants occurred with greater frequency in women (72%). A higher percentage of participants aged <50 years (72.5%) were overweight/obese than those aged 50–64 (70%) and 65+ (61.4%). Level of ID and residence type were significantly associated with weight status (P < 0.001), with overweight/obesity more prevalent in mild (85.7%) than moderate (72%) or severe/profound ID (51.4%). Of those who lived independently/with family, 78.4% were overweight/obese, as were 74% living in a community group home (P < 0.001). Almost all overweight/obese participants’ waist measurements were in the substantially increased risk of metabolic disease waist measurement category (92%, P < 0.001). Logistical regression used to model CHCs on BMI showed significant association between BMI and gastrointestinal tract [odds ratio (OR) = 0.57, P < 0.008, 95% confidence interval (CI) = (0.37; 0.86)], respiratory condition [OR = 8.95, P < 0.004, 95% CI = (2.57; 56.72)] and musculoskeletal disorders [OR = 0.40, P < 0.001, 95% CI = (0.25; 0.63)]. Conclusions: The findings illustrate the strong cross-sectional association between overweight/obesity and CHCs. These findings suggest a need to prioritise weight status as a health risk to people with ID as they age.
PUBLISHED
Keywords: body mass index; chronic health conditions; intellectual disability; obesity; overweight; Ageing; BMI/Obesity; BODY MASS INDEX; CHRONIC HEALTH EVALUATION; CHRONIC ILLNESS; Intellectual Disability; OBESITY; OVERWEIGHT; Age-related disability; Chronic Health Condition; Intellectual Disability; Health